Analisis Putusan Nomor 02/Pid.Sus Anak/2022/PN Crp Tentang Tindak Pidana Narkotika Pada Anak - Rizki, Rizki; Sembiring, Aldho Epranta; Jerry, Joyceline; Jerry, Enrico Houston (Legalitas: Jurnal Hukum, 2024)
Legal infractions pertaining to children in our day of modernity, include instances where children are the offenders, witnesses, or victims of the law. The criminal law pertaining to drugs is one of the laws that is most frequently broken. The author of this study employs a normative juridical approach technique, first doing literature research before examining and evaluating how legal norms—which ought to be applied in conformity with legal rules—are applied. As mentioned in Law Number 35 of 2009 concerning Narcotics, which governs criminal penalties to act as a disincentive to those who misuse and trade in illegal narcotics and their precursors. Observing and analyzing the law as well as theoretical issues pertaining to legal principles, legal history, and legal comparisons that address the application of the law against minors who commit drug-related crimes and legal considerations surrounding decision Number 00/Pid. Sus-anak/2022/PN Crp regarding drug-related crimes against minors are the methods used in the normative juridical approach. The Curup District Court's ruling in case number 00/Pid.Sus Anak/2022/PN/Crp, which dealt with drug misuse in children, was the subject of the author's investigation in this study.